PI3Kγ promotes vascular smooth muscle cell phenotypic modulation and transplant arteriosclerosis via a SOX9-dependent mechanismResearch in context - Qihong Yu; Wei Li; Dawei Xie; Xichuan Zheng; Tong Huang; Ping Xue; Bing Guo; Yang Gao; Chen Zhang; Ping Sun; Min Li; Guoliang Wang; et al. (EBioMedicine, 2018)
Background: Transplant arteriosclerosis (TA) remains the major cause of chronic graft failure in solid organ transplantation. The phenotypic modulation of vascular smooth muscle cells (VSMCs) is a key event for the initiation and progression of neointimal formation and TA. This study aims to explore the role and underlying mechanism of phosphoinositide 3-kinases γ (PI3Kγ) in VSMC phenotypic modulation and TA. Methods: The rat model of aortic transplantation was established to detect PI3Kγ expression and its role in neointimal formation and vascular remodeling in vivo. PI3Kγ shRNA transfection was employed to knockdown PI3Kγ gene. Aortic VSMCs was cultured and treated with TNF-α to explore the role and molecular mechanism of PI3Kγ in VSMC phenotypic modulation. Findings: Activated PI3Kγ/p-Akt signaling was observed in aortic allografts and in TNF-α-treated VSMCs. Lentivirus-mediated shRNA transfection effectively inhibited PI3Kγ expression in medial VSMCs while restoring the expression of VSMC contractile genes, associated with impaired neointimal formation in aortic allografts. In cultured VSMCs, PI3Kγ blockade with pharmacological inhibitor or genetic knockdown markedly abrogated TNF-α-induced downregulation of VSMC contractile genes and increase in cellular proliferation and migration. Moreover, SOX9 located in nucleus competitively inhibited the interaction of Myocardin and SRF, while PI3Kγ inhibition robustly reduced SOX9 expression and its nuclear translocation and repaired the Myocardin/SRF association. Interpretation: These results suggest that PI3Kγ plays a critical role in VSMC phenotypic modulation via a SOX9-dependent mechanism. Therefore, PI3Kγ in VSMCs may represent a promising therapeutic target for the treatment of TA. Fund: National Natural Science Foundation of China. Keywords: PI3Kγ, Vascular smooth muscle cells, Transplant arteriosclerosis, SOX9, Phenotypic modulation